Peran Suami Dan Petugas Kesehatan Dengan Deteksi Dini Kanker Serviks - Mariene Wiwin Dolang; Christina - Leasa (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
Reproductive Health is a state of complete physical, mental and social well-being that is not solely free from diseases related to the reproductive system. Cervical cancer is cancer that grows from cervical cells, cervical cancer can originate from cells in the cervix but can also grow from cervical cells. This situation is usually accompanied by bleeding and abnormal vaginal discharge. The purpose of this study was to analyze the factors associated with early detection of cervical cancer in fertile age women at Puskesmas Benteng. The design of this study was an observational analytic study with a cross sectional approach. The sample in this study was WUS aged 15-49 years old who were in the Puskesmas Benteng area as many as 135 respondents. The results showed there was a relationship between knowledge (p = 0.004), first age of marriage (p = 0.014), husband's support (p = 0.005), and the role of health workers (p = 0.005) with early detection of cervical cancer in fertile age women at Puskesmas Benteng.DETERMINAN DETEKSI DINI KANKER SERVIKS PADA WANITA USIA SUBUR